ENHANCING CORPORATE SOCIAL RESPONSIBILITY IN INDONESIA: ALIGNING WITH PANCASILA FOR SOCIAL JUSTICE - Jejen Hendar (Universitas Syiah Kuala, 2025)
Corporate Social Responsibility (CSR) is increasingly recognized as a fundamental obligation for companies in Indonesia, closely aligned with the principles of social justice as outlined in Pancasila. Despite this recognition, various challenges persist. The Pancasila framework provides a valuable basis for CSR practices that embody the values of Indonesian society. This study employs a qualitative research approach, gathering data through a comprehensive review of relevant laws and regulations, alongside secondary sources such as books, journals, and research findings. The implementation of CSR regulations encounters several obstacles, underscoring the urgent need for clearer guidelines and robust enforcement mechanisms, including mandatory disclosure in annual reports. Our findings indicate that CSR initiatives often overlook environmental considerations, are hindered by vague implementing rules, and offer crucial insights for companies to preempt regulatory shortfalls. This article stresses the imperative for corporations to address their CSR obligations in ways that foster social justice and benefit local communities. Incorporating Pancasila principles into CSR strategies is essential for their effective realization in Indonesia.